2021
DOI: 10.1038/s41598-021-81411-4
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of people identified as transgender and non-binary gender in Brazil

Abstract: Studies estimate that gender-diverse persons represent 0.1 to 2% of populations investigated, but no such assessment was performed in Latin America. In a representative sample of Brazil’s adult population (n = 6000), we investigated participants' sociodemographic characteristics and possible associations between these and current gender identity, categorized as cisgender, transgender or non-binary gender. We also investigated transgender individuals' distress associated with gender-related body characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
25

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 28 publications
3
48
0
25
Order By: Relevance
“…Há poucos estudos com detalhamento sobre o número de pessoas transexuais e travestis no Brasil, mas pesquisas realizadas em diversas populações mundiais concluíram que correspondem a 0,5% a 1,3% da população geral (Winter et al, 2016). Indivíduos brasileiros com qualquer diversidade de gênero parecem representar cerca de 2% da população adulta do país e estão distribuídos homogeneamente pelas 5 regiões (Spizzirri et al, 2021).…”
Section: Resultsunclassified
“…Há poucos estudos com detalhamento sobre o número de pessoas transexuais e travestis no Brasil, mas pesquisas realizadas em diversas populações mundiais concluíram que correspondem a 0,5% a 1,3% da população geral (Winter et al, 2016). Indivíduos brasileiros com qualquer diversidade de gênero parecem representar cerca de 2% da população adulta do país e estão distribuídos homogeneamente pelas 5 regiões (Spizzirri et al, 2021).…”
Section: Resultsunclassified
“…The amount of people not classified as cisgender within a population can range from 0.1 to 2%. 7 In Brazil, this number can be approximately 2% of adults, which is equivalent to 3 million people. 8 According to the National Association of Transvestites and Transsexuals [ANTRA], 9 90% of the population in the country uses prostitution for their livelihood and as a way of earning income.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, there is a lack of information on transgender and gender-nonconforming people estimates and population profile, although a recent study has shown that gender diversity in the country covers about 2% of the adult population, almost three million people [ 4 ]. There are numerous limitations in tracing a GD epidemiological profile and estimating the need for specialized health services (especially involving surgical interventions) such as: terminological variability in describing transgender identities, different medical and surgical procedures are offered to individuals with GD globally [ 3 ].…”
Section: Introductionmentioning
confidence: 99%